New Cerebral Microbleeds After Mechanical Thrombectomy for Large-Vessel Occlusion Strokes. Issue 47 (November 2015) - Shi, Zhong-Song; Duckwiler, Gary R.; Jahan, Reza; Tateshima, Satoshi; Gonzalez, Nestor R.; Szeder, Viktor; Saver, Jeffrey L.; Kim, Doojin; Ali, Latisha K.; Starkman, Sidney; Vespa, Paul M.; Salamon, Noriko; et al.
Abstract : Abstract: The interval appearance of cerebral microbleeds (CMBs) after endovascular treatment has never been described. We investigated the frequency and predictors of new CMBs that developed shortly after mechanical thrombectomy for acute ischemic stroke, and its impact on clinical outcome. We retrospectively analyzed patients with large-vessel occlusion strokes treated with Merci Retriever, Penumbra System, or stent-retriever devices. Serial T2*-weighted gradient-recall echo (GRE) magnetic resonance imaging (MRI) before and 48 h after endovascular thrombectomy were assessed to identify new CMBs. We examined independent factors associated with new CMBs after mechanical thrombectomy. We analyzed the association of the presence, burden, and distribution of new CMBs with clinical outcome. A total of 187 consecutive patients with serial GRE were enrolled in this study. CMBs were evident in 36 (19.3%) patients before mechanical thrombectomy. New CMBs occurred in 41 (21.9%) patients after mechanical thrombectomy. Of the 68 new CMBs, 45 appeared in the lobar location, 18 in the deep location and 5 in the infratentorial location. The presence of baseline CMBs was associated with new CMBs after mechanical thrombectomy (OR 5.38; 95% CI 2.13–13.59; P  < 0.001), no matter whether the patients were treated primarily with mechanical thrombectomy or with intravenous thrombolysis followed by mechanical thrombectomy. Patients with new CMBs did not have increased rates of hemorrhagic transformation, in-hospital mortality, and modified Rankin Scale score 4 to 6 at discharge. New CMBs are common after mechanical thrombectomy in one-fifth of patients with acute ischemic stroke. Baseline CMBs before mechanical thrombectomy predicts the development of new CMBs. New CMBs after mechanical thrombectomy do not influence clinical outcome.